Distribution of hsp65 PCR-Restriction Enzyme Analysis Patterns among Mycobacterium avium Complex Isolates in Thailand - Therdsak Prammananan; Saranya Phunpruch; Nipa Tingtoy; Somboon Srimuang; Angkana Chaiprasert (My University, 2006)
ABSTRACT A total of 227 clinical Mycobacterium avium complex isolates from Thailand were differentiated into species and types by using PCR-restriction enzyme analysis of hsp65 . The distribution of types showed the predominance of M. avium I (77%) in blood specimens, whereas M. intracellulare I was more commonly found in pulmonary specimens (44.2%). In addition, infections with M. avium were more likely to be found in younger adults (20 to 39 years old), while infections with M. intracellulare were more likely to be found in older adults (≥60 years old). Our results provide the useful epidemiological information that some particular types have more invasive and virulent characters than others.
Keywords: Mycobacterium avium complex; Mycobacterium avium-intracellulare infection; Mycobacterium research and diagnosis